2023
DOI: 10.3389/fendo.2023.1175548
|View full text |Cite
|
Sign up to set email alerts
|

Concerns and expectations in women with polycystic ovary syndrome vary across age and ethnicity: findings from PCOS Pearls Study

Mirna Elghobashy,
Gar Mun Lau,
Meri Davitadze
et al.

Abstract: ObjectiveTo understand and explore the perceptions and opinions of women with polycystic ovary syndrome (PCOS) and further delineate the variations across age and ethnicity.DesignQualitative survey focussed on lived experiences of people with PCOS. Participants could share their views either as written text or as voice note audio recording(s) on WhatsApp. The data from the audio were transcribed verbatim. Responses were coded by two study members independently, using a thematic inductive method with NVivo 12. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Our study revealed that 65.2% PCOS subjects reported being overweight or obese, significantly more than non-PCOS subjects. Obesity has been linked to depression in the general female population, and around two thirds of women with PCOS are overweight or obese [27], in accord with the study findings here where increasing obesity led to greater dissatisfaction that was in accord with a meta-analysis showing lower scores in the weight subscale for the Body Esteem Scale for Adolescents and Adults [7], and reflected those in the lived experience study in PCOS where feeling less feminine was in part related to weight gain [8]. Obesity has been shown to increase the likelihood of losing self-esteem and developing a negative body…”
Section: Plos Onesupporting
confidence: 86%
See 1 more Smart Citation
“…Our study revealed that 65.2% PCOS subjects reported being overweight or obese, significantly more than non-PCOS subjects. Obesity has been linked to depression in the general female population, and around two thirds of women with PCOS are overweight or obese [27], in accord with the study findings here where increasing obesity led to greater dissatisfaction that was in accord with a meta-analysis showing lower scores in the weight subscale for the Body Esteem Scale for Adolescents and Adults [7], and reflected those in the lived experience study in PCOS where feeling less feminine was in part related to weight gain [8]. Obesity has been shown to increase the likelihood of losing self-esteem and developing a negative body…”
Section: Plos Onesupporting
confidence: 86%
“…Within the 2023 international PCOS guidelines, there is the inclusion of body image as a new recommendation for the assessment in PCOS management [ 6 ], and a systematic review highlighted the body image concerns that women with PCOS have [ 7 ]. In a qualitative lived experiences in PCOS study poor mental health, dermatological and menstrual issues were highlighted, together with the report that more than half felt less feminine, and these also varied with ethnicity [ 8 ]. The term "body image" refers to a person’s perception of their body regarding their appearance, size, health, normal functioning, and sexual desires [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…PCOS can manifest with various symptoms across different life stages, including reproductive, dermatological, metabolic, and psycho-socio-sexual problems ( 2 ). Despite this multifaceted nature, the psychological, emotional, and social aspects associated with PCOS often receive inadequate attention in clinical practice, leaving many adolescents and women dissatisfied with the prevailing standard of care ( 3 6 ). Consequently, women with PCOS seek personalised healthcare that can address their specific health concerns, especially focusing on psychological and emotional well-being and resilience ( 7 10 ).…”
Section: Introductionmentioning
confidence: 99%